A Copeptin as a Predictor Marker for Insulin Resistance Among Women with Polycystic Ovary Syndrome - Ali, Alaa I.; Hassan, Wassan N. M.; Alrawi, Sumaya (Current Women's Health Reviews, 2022)
Background: A polycystic ovarian syndrome (PCOS) is a common endocrine syndrome in which women have a wide range of clinical presentations; insulin resistance was linked to its pathogenesis. Objective: We aimed to investigate the copeptin role as a predictive marker of insulin resistance among PCOS women. Materials and Methods: In University Hospital, we included 280 women, with 140 of them being healthy controls. 140 out of 280 cases of PCOS subdivided into two groups depending on the insulin resistance; group 1 with homeostasis model assessment for the insulin resistance < 2.5. Group 2 with homeostasis model assessment for the insulin resistance >2.5. The evaluation of body mass index and blood pressure for all besides the blood sampling for estimation of a follicular stimulating hormone, luteinizing hormone, prolactin, estradiol, sex hormone-binding globulin, total testosterone, fasting insulin dehydroepiandrosterone sulfate, C-reactive protein, plasma glucose, free androgen index, and plasma copeptin using the Copeptin-Human EIA Kit besides the transvaginal ultrasound for ovarian assessment. Results: When compared to other groups, PCOS women with positive insulin resistance >2.5 had a significantly higher plasma copeptin level. The ROC curve calculated a 1.94 pmol/L; plasma copeptin cutoff value for detecting the insulin resistance in PCOS with 88 % sensitivity value and 36 % specificity, AUC was 0.88. Conclusion: The significant positive relationship between serum copeptin and insulin resistance with high sensitivity implies its usefulness as a marker of insulin resistance among PCOS patients with a high prediction of its complication.
Keywords: metabolic syndrome